2018
DOI: 10.3390/coatings8040148
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Fabrication and Localized Electrochemical Characterization of Continuous Al-Alloyed Intermetallic Surface Layer on Magnesium Alloy

Abstract: A continuous intermetallic compound coating was fabricated on AZ91D magnesium alloy via heat treatment at 400 • C in AlCl 3-NaCl molten salts for 10 h. The microstructure and composition of the coating were characterized by scanning electron microscope and energy dispersive X-ray spectrometry. The results showed that the coating has a two-layer structure (the outer Mg 2 Al 3 phase layer and the inner Mg 17 Al 12 phase layer) up to 37 µm thick with compact and planar interfaces between the layers and the substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The resulting R p value is the sum of R 2 and R 3 according to Equation (5). The EC model (Figure 7b) representing the electrochemical corrosion behavior of uncoated AZ91 alloy in 0.1 M NaCl solution after 5 min includes the elements such as R 1 , which is the solution resistance [41]. High-frequency loop characterizing damaged Mg(OH) 2 layer is observed-elements Q 2 and R 2 (Figure 7b).…”
Section: Electrochemical Impedance Spectroscopy Characteristicsmentioning
confidence: 99%
“…The resulting R p value is the sum of R 2 and R 3 according to Equation (5). The EC model (Figure 7b) representing the electrochemical corrosion behavior of uncoated AZ91 alloy in 0.1 M NaCl solution after 5 min includes the elements such as R 1 , which is the solution resistance [41]. High-frequency loop characterizing damaged Mg(OH) 2 layer is observed-elements Q 2 and R 2 (Figure 7b).…”
Section: Electrochemical Impedance Spectroscopy Characteristicsmentioning
confidence: 99%
“…Coatings are fabricated on the surface to enhance the corrosion resistance of magnesium alloys [7][8][9][10][11][12][13][14][15][16][17][18][19]. Among which, the zinc coating is an effective one.…”
Section: Introductionmentioning
confidence: 99%
“…to reduce the corrosion rate of Mg-based alloys [8][9][10][11]. Metallic coatings have been proved to exhibit high corrosion resistance, excellent mechanical property, good biocompatibility and favorable electric conductivity, which can simultaneously enhance the corrosion resistance and surface strength without deteriorating the electric conductivity [12][13][14][15][16]. Jin et al [13] deposited Ta-containing coating on the ZK60 Mg alloy surface by reactive magnetron sputtering and the corrosion resistance and biocompatibility were improved by the modified surface composed of Ta 2 O 5 , Ta suboxide and Ta.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, composite metallic coatings have been prepared to further modify Mg alloys to obtain desirable corrosion rate. Fu et al reported that the corrosion rate of AZ91D Mg alloy was obviously reduced by the Al-Mg intermetallic compound coating fabricated by heat treatment in AlCl 3 -NaCl molten salts, which was attributed to the gradient microstructure of outer Mg 2 Al 3 and inner Mg 17 Al 12 phases formed on the surface [16].…”
Section: Introductionmentioning
confidence: 99%